Pathogenicity and host specificity of Brazilian and African isolates of the acaropathogenic fungus Neozygites tanajoae to mite species associated with cassava - Agboton, B.V.; Hanna, R.; Hountondji, F.C.C.; Tiedemann, A. von (Wiley, 2009)
Neozygites tanajoaeis a host-specific acaropathogen introduced in the late1990s from Brazil into cassava fields in West Africa for biocontrol ofthe cassava green mite (Mononychellus tanajoa). Local African isolates ofN. tanajoaeare morphologically similar to introduced Brazilian strainsbut the two origins can be distinguished by diagnostic PCR. In this studyit was explored whether differential traits in acaropathogenic perfor-mance and host specificity exist between Brazilian and African isolates.Pathogenicity and host specificity of two Brazilian and two Africanisolates ofN. tanajoaewere compared in leaf discs laboratory bioassaysor on whole cassava plants in the greenhouse by exposing adult femalemites to inoculum delivered fromN. tanajoaeinfested mite mummies.The results show that all fourN. tanajoaeisolates caused significant mor-tality ofM. tanajoa,both on leaf discs and on whole plants. However, onleaf discs the Brazilian isolate collected directly from Alto Alegre inBrazil (Brazil–Brazil isolate) caused a significantly higher mortality(80%) than the Brazilian isolate collected about 9 years post-releasefrom a field in Adjohoun (Brazil–Benin isolate) (61.3%). The two Afri-can isolates collected in Benin and Tanzania caused a mortality similarto the African–Brazilian isolate (62.3% and 61.3% respectively).Onwhole cassava plants, the four fungal isolates did not show any signifi-cant differences in incidence ofM. tanajoainfection. The host specificitystudy was conducted on leaf discs against a collection of mite speciestypically associated with cassava plants in Africa,Typhlodromalus aripo,Euseius fustis,Tetranychus urticaeandOligonychus gossypii. It demonstratedthat the African and Brazilian isolates ofN. tanajoaehad similar hostspecificity forM. tanajoa.